Invite Only Dinner with Bernard Witkin at Basque Hotel - Watkins, Howard::::::::: (1986)
Judge James V. Paige standing and telling a story about Bernard Witkin; on left: ?, Justice Hollis Best and Judge Robert Mardikian; head table: Judge Frank Creede, Jr., Bernard Witkin and Judge Robert Coyle; Facing Judge Paige: Jack Baker, Jim Barstow, Judge Leonard Meyers and Peter Morris; Backside on right: Justice Charles Hamlin and Judge Gene Gomes